Effect of hydrogen ion concentration and adsorbent dosage on the removal of heavy metals from metal scrap effluents using activated carbon from African palm fruit - Abdullahi, Zalihat; Hussaini, Kamaludeen; Abdulrazak, Sani; Hashimu Yau, Abdulwahab (International Journal of Advanced Chemistry, 2019)
This study details the production of activated carbon from African palm fruit and subsequent treatment of heavy metals; Cadmium, Copper, Nickel, and Lead in wastewater effluent with the produced activated carbon from a metal scrap market in the heart of Kaduna state, Nigeria, which constitutes high level of pollution in the environment. Hydrogen ion concentration and adsorbent dosage were determined on water treatment quality using Atomic Absorption Spectrophotometer (AAS). The produced activated carbon showed a significant ability in removing heavy metals; Cadmium, Copper, Nickel, and Lead from samples of the wastewater. Higher efficiencies were observed with increase in adsorbent dosage (99.73 ± 0.265, 95.96 ± 0.053, 99.91 ± 0.085, and 95.12 ± 0.035 % at 2.5 g for Cadmium, Copper, Nickel, and Lead, respectively) and at a pH of 6 (99.61 ± 0.182 and 80.31 ± 0.015 % for Cadmium and Lead, respectively) and at a pH of 8 ( 99.79 ± 0.201 and 99.73 ± 0.252 for copper and nickel respectively). This findings show that African palm fruit can be utilized to produce activated carbon used in removal heavy metals from effluent water, representing an effective means of utilizing agricultural residues and also an alternative to the expensive commercial activated carbon.